A new species of the genus Anthaxia Eschscholtz, 1829 from southern Africa (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2014)
Anthaxia (Haplanthaxia) vlasta sp. nov. from the southern part of the Ethiopian Region (Malawi, Republic of South Africa, Rwanda, Tanzania, Zimbabwe) is described and illustrated. Its isolated position among the Ethiopian species-groups is briefly discussed.